Gambaran Subjective Well-Being pada Mahasiswa yang Bekerja pada Mahasiswa Fakultas Keguruan dan Ilmu Pendidikan Universitas Syiah Kuala - Rahmiyati, Evi; Izzah, Hida Yatul; Bakar, Abu; Nurhasanah, Nurhasanah (LP. Ma'arif Janggan Magetan, 2024)
One of the factors that influences subjective well-being in working students is their ability to divide their time, attention and energy equally between studies, personal life and work. This research aims to determine the subjective well-being picture of students who work at the Faculty of Teacher Training and Education, Syiah Kuala University, Banda Aceh. This research is quantitative research. The population of this study were all FKIP students at Syiah Kuala University who studied while working. This research sample consisted of 73 students, with a sampling technique using total sampling. Data collection was carried out using a questionnaire consisting of 36 statement items. The results of the research show that the average subjective well-being picture for students working at the Faculty of Teacher Training and Education, Syiah Kuala University, Banda Aceh, is 50.7%, which is in the high category. So it can be concluded that the average student who works at the Faculty of Teacher Training and Education, Syiah Kuala University, Banda Aceh, already has a high subjective well-being..